THE CRUCIAL ROLE OF MAGNETIC RESONANCE IMAGING IN DIAGNOSING AND STAGING SPINAL TUMORS CAUSING NEUROLOGICAL DEFICIT (The Research of Medical Science Review, 2025)
Background: Spinal tumors can cause serious neurological deficits if not identified early. MRI is a reliable, non-invasive tool for detecting and staging these tumors, providing detailed insights into their type, location, and impact. Understanding MRI findings in relation to neurological symptoms is key to early diagnosis and effective treatment planning. Methodology: This research was a prospective analytical study. Data was collected from the Radiology Department of Nishtar Hospital, Multan. A total of 73 patients with spinal tumors causing neurological deficits were included. Data was analyzed using SPSS. Results: Among 73 spinal tumor patients (mean age 31.97 ± 14.15 years), 52.1% were male. Meningioma was most common (35.6%), followed by glioma (27.4%), neurofibroma (20.5%), and schwannoma (16.4%). Paralysis was present in all glioma cases and 93.3% of neurofibromas. Visual changes (49.3%), bladder dysfunction (53.4%), muscle weakness (52.1%), pain (53.4%), and numbness (47.9%) were frequently observed, varying by tumor type.MRI showed hypointensity on T1 in 57.5% and hyperintensity on T2 in 86.3% of cases. All gliomas were intramedullary; others were extramedullary. Grade 3 tumors were most frequent. MRI effectively correlated imaging features with neurological deficits. Conclusion: This study points out the crucial role of MRI in the diagnosis and staging of spinal tumors with neurological deficits. Gliomas were highly associated with paralysis and bladder dysfunction, whereas meningiomas, neurofibromas, and schwannomas occurred in a variable fashion with pain, numbness, and visual disturbances. MRI correctly differentiated the types of tumors, grades, and locations, and T1 hypointensity and T2 hyperintensity were frequent findings.